Sprint performance and force-velocity profiling does not differ between artificial turf and concrete - Shahab, S.; Steendahl, I. B.; Ruf, L.; Meyer, T.; Van Hooren, B. (International Journal of Sports Science & Coaching, 2021)
Purpose: Force-velocity-power (F-v-P) profiling can illustrate an individual`s sprinting capabilities, but no study has explored the effect of different running surfaces on F-v-P outcomes.